Solo, pair or Mob programming: Which should be used in university? - Ramón Ventura Roque Hernández; Sergio Armando Guerra Moya; Adán López Mendoza (Universidad de Guadalajara, 2020)
The aim of this research is to compare individual, pair and Mob programming in university programming courses taking into account the perceptions of the students. 24 students participated in a course of Intermediate programming with Visual Basic. Net. They worked with the three modalities in the development of software projects during regular class sessions. A sequential explanatory mixed research design was used. For the quantitative component, questionnaires were administered. For the qualitative section, interviews were conducted. The results showed that students prefer pair programming because they perceive it as a midpoint between programming alone and doing it with a large group. Solo programming may cause stress and intellectual blockage, and doing so with too many people at the same time may generate distraction and imbalance of work among the participants. A limitation of the study is the sample size. However, the work makes quantitative and qualitative contributions in an area of knowledge little explored in formal literature. The findings suggest promoting work in pairs in university programming courses, as it is easily implemented with few resources and good results.